Efficiency of three buffers for extracting β-glucosidase enzyme in different soil orders: Evaluating the role of soil organic matter - Gutiérrez, Viviana (2017)
The objective of this research was to evaluate extraction methods for β-glucosidases comparing three buffer solutions (MUB, acetate, and maleate) at different incubation times (0.5 h to 10 h) and in three different soil orders (Mollisols, Andisols and Ultisols). Seven acidic soils were evaluated, showing differences in pH, OM, and clay contents. To evaluate the effect of OM as enzymes source, one soil of each order was treated to partially remove its OM and then the enzyme assay was performed. When using MUB and maleate buffers the highest (32 and 31 µg-pNP g-soil-1h-1 in average, respectively) were found, and the latter was significantly (p < 0.050) correlated with the soil clay content. The activity obtained with acetate buffer was much lower (38.2 µg-pNP g-soil-1h-1 in average). The use of MUB buffer with 1 h of incubation is suggested as extraction method, showing good reproducibility and allowing to express higher enzyme potential for soil comparisons. For the Andisol and Ultisol, the enzyme activity significantly decreased with the OM removal (%) indicating that OM is the major source of the measured β-glucosidase activity, while a different trend was observed for the Mollisol, in which the mineral fraction (mainly 2:1 type clay) appears to be involved in the increased enzyme activity displayed after the initial OM removal.